Phase-specific changes in rate of force development and muscle morphology throughout a block periodized training cycle in weightlifters - Suarez, D. G.; Mizuguchi, S.; Hornsby, W. G.; Cunanan, A. J.; Marsh, D. J.; Stone, M. H. (Sports, 2019)
The purpose of this study was to investigate the kinetic and morphological adaptations that occur during distinct phases of a block periodized training cycle in weightlifters. Athlete monitoring data from nine experienced collegiate weightlifters was used. Isometric mid-thigh pull (IMTP) and ultrasonography (US) results were compared to examine the effects of three specific phases of a training cycle leading up to a competition. During the high volume strength-endurance phase (SE) small depressions in rate of force development (RFD) but statistically significant (p = 0.05) increases in vastus lateralis cross-sectional area (CSA), and body mass (BM) were observed. The lower volume higher intensity strength-power phase (SP) caused RFD to rebound above pre-training cycle values despite statistically significant reductions in CSA. Small to moderate increases only in the earlier RFD time bands (<150 ms) occurred during the peak/taper phase (PT) while CSA and BM were maintained. Changes in IMTP RFD and CSA from US reflected the expected adaptations of block periodized training phases. Changes in early (<100 ms) and late (=150 ms) RFD time bands may not occur proportionally throughout different training phases. Small increases in RFD and CSA can be expected in well-trained weightlifters throughout a single block periodized training cycle